Who Is Willing to Migrate in the CEECS? Evidence From the Czech Republic - Peter Huber; Jan Fidrmuc (European Regional Science Association (ERSA), 2006)
This paper explores the willingness to migrate in the Czech Republic. We find that variables measuring regional labour market conditions and amenities contribute little to explaining the willingness to migrate, but that personal and household characteristics are more important. Persons owning family houses are substantially less willing to migrate and the relationship between the willingness to migrate and income is U shaped, persons experiencing longer unemployment spells are not less willing to migrate and commuting may at least partially compensate for low willingness to migrate. Finally, with the exception of the less educated, the willingness to migrate of all groups analysed reacts only weakly to regional labour market conditions and amenities.
Keywords: 330